A Prospective Cohort Study Investigating the Behavioural Development of Bitches in a Guide Dog Training Programme Neutered Prepubertally or Post-Pubertally - Moxon, Rachel; Freeman, Sarah; Payne, Richard; Corr, Sandra; England, Gary C. W. (Frontiers in Veterinary Science, 2022)
There are few studies which investigate the effect of neutering bitches before or after puberty. The majority of current literature examining the impact of the timing of neutering on health and behaviour has used age rather than onset of puberty as the key variable. The aim of this prospective cohort study was to investigate the effects of timing of neutering in relation to puberty on behaviour in female dogs reared and trained in an assistance dog programme. The study examined data for bitches neutered before or after puberty to compare scores for six behavioural factors (Training and obedience, Aggression, Fear and anxiety, Excitability, Attachment and attention-seeking, Social behaviour) measured at one and three-years of age. Labrador and Golden Retriever crossbreed bitches were neutered before (n=155) or after (n=151) puberty. Neutering before or after puberty had no impact on mean scores for the six behavioural factors at one or three years of age. When examining the change in behavioural factor scores between one and three years of age, only Aggression behavioural factor scores were influenced by neutering before or after puberty. Bitches neutered after puberty were less likely to have Aggression factor scores which increased between one and three years of age (OR = 0.959, 90% CI = 0.924 to 0.995, P = 0.06). However, the majority of bitches scored ‘0’ for Aggression at both time points (indicating no aggression behaviours were observed) and the number of bitches for which scores increased between one and three years of age was low (before puberty = 20, after puberty = 9). This is consistent with very mild aggressive behaviours being observed in a small number of animals and is therefore of questionable concern. The results suggest that for Labrador and Golden Retriever crossbreed bitches, neutering before or after puberty has little to no effect on future behaviour. It is recommended that decisions about the timing of neutering are not informed solely by impacts on behaviour, but that they also consider evidence relating to the impacts on bitch health and wellbeing.